1982
DOI: 10.1007/bf02629543
|View full text |Cite
|
Sign up to set email alerts
|

Malignant melanoma of the anus

Abstract: The authors present a report of 12 patients with anal melanoma (AM) and review 255 cases reported since 1947. Combining these patients with those from the literature, the authors analyze several aspects of AM that are controversial or have not been studied in a systematic manner. The mean clinical tumor size was 4.1 cm. Seventy per cent were grossly pigmented, 63 per cent were polypoid, and 44 per cent were prolapsed. Two-thirds of AM were located in the proximal pecten, at or near the level of the anal valves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
7

Year Published

1988
1988
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(31 citation statements)
references
References 25 publications
2
19
0
7
Order By: Relevance
“…The clinical diagnosis may be incorrect in 80% of all cases [1, 2, 18]. Because of delayed diagnosis and rapid progression, malignant rectal melanomas have been accompanied by distant metastases in 60% of patients at the time of final diagnosis [4, 13]. The two present cases had a chief complaint of rectal bleeding, and clinical diagnosis before surgery was rectal carcinoma.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The clinical diagnosis may be incorrect in 80% of all cases [1, 2, 18]. Because of delayed diagnosis and rapid progression, malignant rectal melanomas have been accompanied by distant metastases in 60% of patients at the time of final diagnosis [4, 13]. The two present cases had a chief complaint of rectal bleeding, and clinical diagnosis before surgery was rectal carcinoma.…”
Section: Discussionmentioning
confidence: 97%
“…Malignant melanomas occur frequently in the anorectum because of the presence of abundant melanocytes in the mucosa of the anal canal. The reported 5-year overall survival rate is 6%–15% of patients after surgery [4, 5, 7, 1113]. Several studies have reported cases of long-term survival [1416].…”
Section: Discussionmentioning
confidence: 99%
“…Surgery as a primary treatment strategy for PAMM, ranges from abdominoperineal resection (APR) to wide local excision (WLE). However, previous studies comparing the difference in survival time of patients treated by APR or WLE identified no statistical difference (10,13). In a number of studies, adjuvant chemotherapy (14), adjuvant radiation (15), neoadjuvant radiation (16) and immunotherapies (17) have also been used in PAMM, and certain curative effects were obtained.…”
Section: Discussionmentioning
confidence: 86%
“…Traditionally, APR is regarded as the standard surgery for AMM [7,21,22]. APR is preferred because it can control lymphatic spread (mainly to mesenteric lymph nodes) and guarantee a larger negative margin for local control [23].…”
Section: Surgical Treatmentmentioning
confidence: 99%